Предмет: Алгебра,
автор: kaneky
преобразовать произведение в многочлен
(x+y)(z+1)=
(x+2)(y-z)=
(x-1)(x+y-3)=
(x-y)(x+y)=
(x+1)(x+1)=
Ответы
Автор ответа:
2
1) xz+x+yz+y
2) xy-xz+2y-2z
3)
![{x }^{2} + xy - 3x - x - y + 3 = {x}^{2} + xy - 4x - y + 3 {x }^{2} + xy - 3x - x - y + 3 = {x}^{2} + xy - 4x - y + 3](https://tex.z-dn.net/?f=+%7Bx+%7D%5E%7B2%7D++%2B+xy+-+3x+-+x+-+y+%2B+3+%3D++%7Bx%7D%5E%7B2%7D++%2B+xy+-+4x+-+y+%2B+3)
4)
![{x}^{2} - {y}^{2} {x}^{2} - {y}^{2}](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D+)
5)
![{x}^{2} + x + x + 1 = {x}^{2} + 2x + 1 {x}^{2} + x + x + 1 = {x}^{2} + 2x + 1](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%2B+x+%2B+x+%2B+1+%3D++%7Bx%7D%5E%7B2%7D++%2B+2x+%2B+1)
2) xy-xz+2y-2z
3)
4)
5)
Похожие вопросы
Предмет: Другие предметы,
автор: tatanaradcenko101
Предмет: Алгебра,
автор: userx550076
Предмет: Физика,
автор: lera11223340
Предмет: Алгебра,
автор: franklinOC
Предмет: Химия,
автор: alexnas